SPATIAL DISTRIBUTION OF HOTSPOTS USING S-NPP VIIRS FOR EARLY DETECTION OF POTENTIAL FIRE - Rosalina Kumalawati; Avela Dewi; Astinana Yuliarti; Rizky Nurita Anggraini; Karnanto Hendra Murliawan (Universitas Sebelas Maret (UNS), 2023)
Fire is a disaster and its frequency is increasing every year. Seeing this, it is very important to know the spatial distribution of hotspots to determine the potential for fires in each area. Based on this, it is necessary to conduct research with the title